Small for Gestational Age-Cognitive Performance From Infancy to Adulthood: An Observational Study. Issue 5 (May 2021) - Eves, R.; Mendonça, M.; Bartmann, P.; Wolke, D.
Abstract : (Abstracted from BJOG 2020;127(13):1598–1606) Understanding the impact of being born small for gestational age (SGA) on cognitive performance is complicated. While SGA has been associated with lower developmental and intelligence test scores (IQ) in childhood, studies on its effects into adulthood are unclear.